2013
DOI: 10.1155/2013/960821
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarriers for Diagnosis and Targeting of Breast Cancer

Abstract: Breast cancer nanotherapeutics is consistently progressing and being used to remove the various limitations of conventional method available for the diagnosis and treatment of breast cancer. Nanoparticles provide an interdisciplinary area for research in imaging, diagnosis, and targeting of breast cancer. With advanced physicochemical properties and better bioavailability, they show prolonged blood circulation with efficient tumor targeting. Passive targeting mechanisms by using leaky vasculature, tumor microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 67 publications
1
50
0
Order By: Relevance
“…Nanotechnologies offer promising approaches for the diagnosis and treatment of neoplastic disease, which remains a major on-going public health concern (Sharma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnologies offer promising approaches for the diagnosis and treatment of neoplastic disease, which remains a major on-going public health concern (Sharma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, carbon nanotubes (CNTs) have been envisioned in designing novel delivery platforms for medical applications due to their unique physical and chemical properties [1][2][3][4]. The physicochemical versatility of these nanomaterials is related to a large inner volume that can be filled with the desired chemical small molecules and multiple attachment sites for various functional groups along the nanotube axis [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…NPs as carrier can reduce the cytotoxic side effects and achieve targeting chemotherapy. 22,23 We had previously evaluated the application of NPs and found that it would provide a promising strategy for chemotherapy. …”
Section: Discussionmentioning
confidence: 99%